2012
DOI: 10.1186/1746-6148-8-218
|View full text |Cite
|
Sign up to set email alerts
|

O6-methylguanine-DNA methyltransferase in equine sarcoids: molecular and epigenetic analysis

Abstract: BackgroundBovine papillomaviruses (BPVs) types 1 and 2 are the only known papillomaviruses able to jump the species. In fact, BPVs 1/2 induce neoplasia in their natural bovine host but infection is also associated to neoplastic skin lesions in equids termed sarcoids. The equine sarcoid is considered to be the most common equine cutaneous tumour worldwide for which no effective therapy is available. Very little is known about the molecular mechanisms underlying tumourigenesis, although genes contributing to sar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…A recent study by Mählmann et al revealed, in diseased tissues, elevated transcript levels of the FOXP3 ( Forkhead Box P3 ) gene, which encodes protein involved in immune response. In turn, Altamura et al and Strazzullo et al showed under‐expression of the DNA‐repair gene MGMT ( O‐6‐methylguanine‐DNA Methyltransferase ) and of the putative tumour suppressor gene FHIT ( Fragile Histidine Triad ). However, these observations were not confirmed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Mählmann et al revealed, in diseased tissues, elevated transcript levels of the FOXP3 ( Forkhead Box P3 ) gene, which encodes protein involved in immune response. In turn, Altamura et al and Strazzullo et al showed under‐expression of the DNA‐repair gene MGMT ( O‐6‐methylguanine‐DNA Methyltransferase ) and of the putative tumour suppressor gene FHIT ( Fragile Histidine Triad ). However, these observations were not confirmed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Equine sarcoid is the most common cancer of the horse . This nonmetastasizing skin tumor is strongly associated with infection by BPV1 and BPV2 2 and thus appears to be a rare example of cross‐species infection by a papillomavirus . However, there is also evidence for sequence variants of BPV1 in sarcoids, which may indicate that sarcoid is caused by horse‐specific BPV1 variants.…”
Section: Discussionmentioning
confidence: 99%
“…3 This nonmetastasizing skin tumor is strongly associated with infection by BPV1 and BPV2 2 and thus appears to be a rare example of cross-species infection by a papillomavirus. 26 However, there is also evidence for sequence variants of BPV1 in sarcoids, 27 which may indicate that sarcoid is caused by horse-specific BPV1 variants. The primary goal of this study was to determine if a SNP array-based GWAS would detect an association between susceptibility to sarcoid and allelic variants in the Major Histocompatibility Complex of the horse.…”
Section: Discussionmentioning
confidence: 99%
“…The E7 protein cooperates in evading innate immunity [19][20][21][22][23][24][25][26][27]. The oncogenesis of equine sarcoids also involves loss of expression of the Fragile Histidine Triad (FHIT) and of the O 6 -methylguanine-DNA methyltransferase (MGMT) tumor suppressor proteins [28,29]. Recent studies have evaluated the role of small non-coding RNAs that regulate gene expression (microRNAs) in the development of sarcoids, and the role of aberrant methylation (S100A14 gene) is under research [30][31][32][33][34].…”
Section: Etiopathogenesis Of the Equine Sarcoid 21 Bovine Papillomavmentioning
confidence: 99%